Endocan (ESM-1) levels in gingival crevicular fluid correlate with ICAM-1 and LFA-1 in periodontitis - Mahmure Ayşe Tayman; Canan Önder; Şivge Kurgan; Muhittin Abdulkadir Serdar; Meral Günhan (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: Endocan, a 50 kDa soluble proteoglycan, also called endothelial cell-specific molecule-1 (ESM-1), is involved in many major cellular activities and has been reported to be overexpressed in inflammatory conditions. This study aims to determine ESM-1 levels in gingival crevicular fluid (GCF) samples from individuals with periodontitis to determine the correlation between the levels of lymphocyte-function-associated antigen-1 (LFA-1), intercellular adhesion molecule-1 (ICAM-1), and clinical findings of periodontitis. This study enrolled 27 individuals diagnosed with Stage III-Grade C generalized periodontitis and 16 individuals as healthy controls. Bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL) were calculated. Enzyme-linked immunosorbent assay (ELISA) test was used for detecting the levels of ESM-1, ICAM-1, and LFA-1 in GCF samples. PPD, BOP, CAL, and GCF volumes were significantly increased in patients with periodontitis in comparison to the control group (p < 0.001). The total amount of ESM-1, ICAM-1, and LFA-1 levels in GCF were increased in the periodontitis group (p < 0.001). ESM-1 level correlated with PPD, BOP, and CAL (p < 0.05). ICAM-1 level correlated with BOP and CAL (p < 0.05). LFA-1 level correlated with PPD and CAL (p < 0.05). Our data indicate that ESM-1, ICAM-1, and LFA-1 levels are increased in GCF of patients with periodontitis. These molecules could be associated with the pathogenesis and progression of periodontal disease.